Hysteresis in unemployment: Evidence from OECD estimates of the natural rate - Laurence M. Ball; Joern Onken (European Central Bank (ECB), 2021)
This paper studies the dynamics of unemployment (u) and its natural rate (u*), with u* measured by real-time estimates for 29 countries from the OECD. We find strong evidence of hysteresis: an innovation in u causes u* to change in the same direction, and therefore has permanent effects. For our baseline specification, a one percentage point deviation of u from u* for one year has a long-run effect of 0.16 points on both variables. When we allow asymmetry, we find, perhaps surprisingly, that decreases in u have larger long-run effects than increases in u.
Keywords: E24; 330; hysteresis; unemployment; natural rate; high-pressure economy